Volume 4A: Structures, Safety and Reliability 2014
DOI: 10.1115/omae2014-23238
|View full text |Cite
|
Sign up to set email alerts
|

Development of Fatigue Damage Model of Wide-Band Process by Artificial Neural Network

Abstract: For the frequency-domain spectral fatigue analysis, the probability mass function of stress range is essential for the assessment of the fatigue damage. The probability distribution of the stress range in the narrow-band process is known to follow the Rayleigh distribution, however the one in the wide-band process is difficult to define with clarity. In this paper, in order to assess the fatigue damage of a structure under wide band excitation, the probability mass function of the wide band spectrum was derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For FDFA, some researchers 2,5,6,8,18,26,27 have devised various frequency-domain models. The TB and Dirlik models are well known for their excellent performance.…”
Section: Frequency-domain Fatigue Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For FDFA, some researchers 2,5,6,8,18,26,27 have devised various frequency-domain models. The TB and Dirlik models are well known for their excellent performance.…”
Section: Frequency-domain Fatigue Analysismentioning
confidence: 99%
“…At present, machine learning models have been applied extensively in the field of fatigue life prediction. 16,17 Kang et al 18 developed an ANN model to fit the complex relationship between the 0th-order spectral moment and shape parameters of a power spectrum and the rainflow amplitude probability function. Durodola et al 15 estimated wideband random fatigue life using an ANN model with the spectral moments of a power spectrum and material parameters as inputs and the fatigue damage as an output.…”
Section: Introductionmentioning
confidence: 99%
“…The relative error of the NN is within 10%. Other studies using FNN for fatigue detection can be found in previous works 171,172,179–200 …”
Section: Review Of Nn Applications In Fatiguementioning
confidence: 99%